(untitled) (ALPHA. Journal of Arts, Literature and Philosophy, 2018)
Starting from highlighting some specific moments in Arendt‟s works critically dealing with sentimentality matters, we will focus on a specific aspect: the place of indignation when narrating, telling, and constructing the history of a community and, at the same time, opening a public space. This is characterized by Arendt as an elementary space, where others appear to me and I appear before them. (Arendt, Human Condition 221), originating the political aspect. This view allows us to rebuild the possible relationship between indignation and politics in this German author‟s views.